Dampak Sosial Media Terhadap Perubahan Sosial di Masyarakat (Studi Kasus Mahasiswa ITB-Indragiri) - Airine Yulianda; Kurnia Dewi; Sry Windartini (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of social media on social change among ITB Indragiri students. Currently, social media not only serves as a communication tool but has also become a lifestyle, influencing interaction patterns and societal perceptions, particularly among the younger generation, in this case, students. The research method used in this study is a qualitative approach with a descriptive approach. The results of the study indicate that social media plays a significant role in social change among students, such as increased access to information, changes in communication patterns, and, more concerning, shifts and changes in social values. While social media offers benefits, such as expanding social networks and accelerating the flow of information, it also has negative impacts, such as the tendency toward addiction, reduced direct interaction, and increased risks of misinformation dissemination.